2022
DOI: 10.4018/ijgbl.294010
|View full text |Cite
|
Sign up to set email alerts
|

Gamification in English as Second Language Learning in Secondary Education Aged Between 11-18

Abstract: Since gamification has strengthened its place in education over the years, it is frequently preferred in English as a Second Language Learning. This study aims to investigate the literature on the effects of gamification on students’ English learning as a second language and the tendency of students to use games to learn English as a second language. This review contains a systematic review of published articles about gamification in English as a Second Language Learning for learners aged between 11-18 from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…On the other hand, there is a significant lack of clear connection between gamification and learning outcomes. These findings are also supported in Kaya and Sagnak's (2022) and Zhang and Hasim's (2023) recent systematic reviews, where most studies reported a positive effect of gamification on learners' language skills, attitudes, and motivation, and found that gamification provides an authentic learning environment. This also applies to systematic reviews of studies on the effectiveness of gamification in mobile and computer assisted language learning (Ishaq et al, 2021;Lin & Lin, 2019;Su et al, 2021), blended learning (Ramalingam et al, 2022), and flipped learning (Ekici, 2021), where positive effects of gamification were found on learners' motivation, academic performance, and engagement.…”
Section: Literature Reviewsupporting
confidence: 68%
See 1 more Smart Citation
“…On the other hand, there is a significant lack of clear connection between gamification and learning outcomes. These findings are also supported in Kaya and Sagnak's (2022) and Zhang and Hasim's (2023) recent systematic reviews, where most studies reported a positive effect of gamification on learners' language skills, attitudes, and motivation, and found that gamification provides an authentic learning environment. This also applies to systematic reviews of studies on the effectiveness of gamification in mobile and computer assisted language learning (Ishaq et al, 2021;Lin & Lin, 2019;Su et al, 2021), blended learning (Ramalingam et al, 2022), and flipped learning (Ekici, 2021), where positive effects of gamification were found on learners' motivation, academic performance, and engagement.…”
Section: Literature Reviewsupporting
confidence: 68%
“…Zhang and Hasim's (2023) systematic review revealed that both learners and teachers held a positive attitude toward gamification mainly because of its capabilities to increase learners' motivation and stimulate their interest and engagement in learning English. Al-Dosakee and Ozdamli (2021) and Kaya and Sagnak (2022) presented similar findings, as they reported a positive effect on learners' motivation, engagement, and overall enjoyment. These findings underscore the significance of the authors' data in this study, since both learners and EFL teachers have perceived the positive effect of gamification on learners' motivation in EFL classes, by now.…”
Section: Perceived Effect On Motivationmentioning
confidence: 53%
“…The paper found that the employment of gamification in teaching vocabulary was significant and improved pupils' vocabulary as a second language among the fifth graders in Iranian schools. Additionally, Kaya (2022) investigated the effect of utilizing gamification in teaching English as a second language in addition to the students' tendency to employ gamification in class. The study included published papers about the utilization of gamification in teaching English as a second language for pupils (11-18) years from 2013 to 2020.…”
Section: Literature Reviewmentioning
confidence: 99%